Birch Memory Web - Mykyta Peregrym (Plant Perspectives)
This narrative non-fiction essay explores the profound and intricate connections between personal memories and birch trees throughout the author’s life. Set against the backdrop of various significant locations, from the Soviet Union and Ukraine to Finnish Lapland, the narrative intertwines the author’s childhood experiences, family history and adult reflections. Birch trees serve as poignant symbols of continuity and resilience amidst the backdrop of political and personal upheavals. The essay delves into how these trees evoke strong emotions and memories, highlighting their unique role as carriers of individual and collective histories. By examining the interplay between nature and memory, the author offers a deeply personal perspective on the importance of preserving natural environments not just for their ecological value but also for their capacity to hold and evoke human experiences.